Polite Speech Acts as a Behaviour of Value of Strengthening Character Education Program in Elementary Schools - Andayani, Andayani; Akbar, Makruf; Situmorang, Robinson (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
One of behavior that is an indicator of the implementation of the value of PPK (Strengthening Character Education) is polite speech acts. polite speech acts is a behavior / speech that is in accordance with manners. This study aims to describe polite speech acts as a behavior of the value of the PPK Program in elementary school. The method used was qualitative approach with descriptive type. The data were collected through informants, namely principals, teachers, and students. Data analysis was carried out with a mileshuberman model, namely data reduction, data display, and data verification. The results of the study showed that some schools have understood the PPK program concept and applied it in one of the behaviors in the form of polite speech acts practiced between teachers and students, students and students in the class. The PPK program in south Tangerang schools, particularly in the form of polite speech acts has been practiced in class. It was expected that polite speech acts could continue so that it takes the habituation of teachers who work with parents of students and students in the form of developing a journal of polite speech acts